Exclusive Breastfeeding Intentions Among Adolescents In Urban Communities In Ibadan, Nigeria - Oluwaponmile A. Odukoya MPH; Musibau A. Titiloye PhD; Oyedunni S. Arulogun PhD (SAGE Publishing, 2022)
Purpose : During adolescence, a female child makes several decisions, and the choice to breastfeed in the near future is conceivably shaped. But in sub-Saharan Africa where teenage pregnancy and teenage motherhood is on the rise, there is a dearth of information on the intention of adolescents to exclusively breastfeed (EBF) in community settings. Therefore, this study assessed exclusive breastfeeding intentions, knowledge and attitude of adolescents in urban communities in Ibadan, Nigeria. Methods : A descriptive community-based cross-sectional study was carried out, selecting 271 respondents. Data were analysed with the aid of IBM SPSS version 21 at P ≤ .05. Results : Mean age of adolescents was 17.5 ± 1.3 years, and 96.3% would breastfeed their children later in future. However, only 37.6%, 22.5% and 50.2% had the intention to exclusively breastfeed, good knowledge score and positive attitude, respectively. There were significant relationships between respondents' age, educational attainment, parents' educational attainment, level of knowledge, attitude and intention. The coefficient of knowledge and attitude were significant predictors of good intention to practise EBF. Major predictors of good intention were good knowledge [OR = 36.5; 95% CI (9.2, 145.2)] and positive attitude toward EBF [OR = 9.7; 95% CI (3.6, 25.9)]. Conclusions : The EBF intention was influenced by multiple factors and should be considered in determining the effectiveness of interventions targeting this practice. Therefore, coherent EBF education interventions that commence from adolescence to promote the practice by adulthood are urgently needed to improve knowledge, attitude and intention about EBF rate and confer the cancer-risk reducing benefits.